ANALYSIS OF EMPLOYEE PERCEPTIONS ON JOB SATISFACTION IN GENERATION Z IN PALU CITY - Pratama, Ramadhan Dio; Rossanty, Niluh Putu Evvy; Wirastuti, Wiri; Risnawati, Risnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine employee perceptions on job satisfaction in generation Z in Palu City. This research uses a quantitative approach with the aim of seeing the relationship between the variables studied. The population of this study was generation Z in Palu City, totaling 35 respondents. The sampling technique on this surveillance uses purposive samplings. This research data collection used a questionnaire. The data analysis technique of this research is descriptive statistics and simple linear regression. Based on the results of descriptive statistics and simple regression analysis conducted, there is a positive and significant influence between Employee Perception (X) on Job Satisfaction (Y) of 64.1%. While the remaining 35.9% is explained by other factors not examined in this study